1986
DOI: 10.1007/bf01296455
|View full text |Cite
|
Sign up to set email alerts
|

Why have controlled trials failed to demonstrate a benefit of esophagogastroduodenoscopy in acute upper gastrointestinal bleeding?

Abstract: Numerous prospective randomized trials have failed to demonstrate a benefit attributable to early diagnostic esophagogastroduodenoscopy (EGD) in acute upper gastrointestinal bleeding (UGIB). The clinical implications of these studies have received extensive editorial comment and analysis. We have employed a probability model to further analyze the reasons why these studies have failed to demonstrate an impact of EGD on UGIB. The clinical course of each bleeding lesion can be predicted from the literature. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 69 publications
0
4
0
1
Order By: Relevance
“…553 Complementing these are studies which deal specifically with the diagnosis for GI related cancers. [554][555][556][557][558][559][560][561] Some research was also found on the use of diagnostic procedures (which were largely effective) such as colonoscopy and biopsy, 562 oesophago-gastroduodenoscopy, 563 imaging techniques (for example, computed tomography, ultrasonography, and MR scan), 553 558 push enteroscopy, 564 and molecular-pathological diagnosis. 565 However, there is also evidence which points to the possible complications which may arise during the treatment of patients or due to the procedures mentioned above, or both.…”
Section: Speed Of Diagnosis and Complications Of Carementioning
confidence: 99%
“…553 Complementing these are studies which deal specifically with the diagnosis for GI related cancers. [554][555][556][557][558][559][560][561] Some research was also found on the use of diagnostic procedures (which were largely effective) such as colonoscopy and biopsy, 562 oesophago-gastroduodenoscopy, 563 imaging techniques (for example, computed tomography, ultrasonography, and MR scan), 553 558 push enteroscopy, 564 and molecular-pathological diagnosis. 565 However, there is also evidence which points to the possible complications which may arise during the treatment of patients or due to the procedures mentioned above, or both.…”
Section: Speed Of Diagnosis and Complications Of Carementioning
confidence: 99%
“…Erst Erickson und Glick [19] Georg Thieme Verlag Stuttgart · New York n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n AKTUELLE CHIRURGIE n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n n [46,47].…”
Section: Notfallendoskopieunclassified
“…Several controlled trials in the 1970s and early 1980s com paring outcome in patients with and without endoscopy failed to show an impact on patient outcome [21][22][23][24]. One explanation postulated for this failure to demonstrate the efficacy of diagnostic endoscopy for upper GI bleeding is that identification of the source of bleeding did not have a significant therapeutic impact prior to the introduction of endoscopic hemostatic therapy [25].…”
Section: Impact Of Endoscopy On Patient Outcomementioning
confidence: 99%